LEGAL ANALYSIS OF CONSUMER PROTECTION OF PUBLIC TRANSPORTATION SERVICES FOR TRAFFIC ACCIDENT VICTIMS - Nabila Azizah Adama; Feibe Engeline Pijoh; Isye Junita Melo (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2025)
Apart from causing casualties such as injuries and deaths, traffic accidents also cause material losses. Material losses resulting from traffic accidents are certainly not small, especially for victims who have experienced physical losses and also experienced material losses, as well as the families of victims who have died There is an obligation for public transportation companies to take responsibility for traffic accidents because the vehicle crew works under the authority of the owner of the public transportation. However, in reality, not all public transportation companies carry out their responsibilities as regulated in statutory regulations. Full legal responsibility often assigned to the vehicle crew who are directly involved in a traffic accident. By using normative legal method, this research aims to find out how consumer protection arrangements for users of public transportation services are regulated and find the right concept of legal protection for consumers who are victims of public transportation traffic accidents. The author finds that consumer protection regulations for users of public transportation services are regulated based on the principles of consumer protection contained in the Law No. 8/1999 concerning Consumer Protection, and are also included in several laws relating to public transportation services, especially roads, namely Law No. 22/2009 concerning Road Traffic Law. Legal protection for consumers who are victims of traffic accidents involving public transportation services is provided through the existing regulations in Consumer Protection Law and Road Traffic Law as well as protection in the so called SWDKLLJ or Mandatory Traffic Accident Fund Contribution mechanism.